0D–3D mixed-dimensional perovskite Cs4Pb(BrCl)6–CsPbBr2−xCl1+x films for stable and sensitive self-powered, high-temperature photodetectors. Issue 46 (16th November 2022) - Ba, Yanshuang; Zhu, Weidong; Huangfu, Sunjie; Xi, He; Han, Tianjiao; Wang, Tianran; Chen, Dazheng; Zhang, Jincheng; Zhang, Chunfu; Hao, Yue
Abstract : 0D Cs4 Pb(BrCl)6 can suppress the cubic to tetragonal phase transition of 3D CsPbBr2− x Cl1+ x in 0D–3D mixed-dimensional Cs4 Pb(BrCl)6 –CsPbBr2− x Cl1+ x films, enabling high-temperature, self-powered PDs with excellent performance and stability. Abstract : Photodetectors with excellent high-temperature performance and facile fabrication are desirable for harsh environment applications. Herein, we report high-temperature, self-powered PDs by adopting 0D–3D mixed-dimensional perovskite Cs4 Pb(BrCl)6 –CsPbBr2− x Cl1+ x films and simple carbon-electrode device configuration. Cs4 Pb(BrCl)6 –CsPbBr2− x Cl1+ x films are prepared through the water-based two-step spin-coating method, wherein the CsCl additive strategy for the PbBr2 precursor film is proposed and it is vital to the target film formation. Based on the optimized Cs4 Pb(BrCl)6 –CsPbBr2− x Cl1+ x film, the self-powered, carbon-electrode PD with outstanding photodetection performance is obtained. It yields a responsivity ( R ) peak of 0.18 A W −1, a specific detectivity ( D *) of 1.65 × 10 13 Jones, and a response time of 1.23 μs. Moreover, 0D perovskite Cs4 Pb(BrCl)6 can suppress the cubic to tetragonal phase transition of 3D perovskite CsPbBr2− x Cl1+ x, and thus the resulting PD can work effectively at ∼300 °C, for which a dark current density of 6.34 × 10 −8 A cm −2, an on/off ratio of over 1.44 × 10 5, and a stable working duration of ∼300 min are achieved, indicating its excellent tolerance to high temperature and ideal compatibility for practical applications.